SCB-HC-ECC–Based Privacy Safeguard Protocol for Secure Cloud Storage of Smart Card–Based Health Care System - Senthilkumar, Sudha; Brindha, K.; Kryvinska, Natalia; Bhattacharya, Sweta; Reddy Bojja, Giridhar (Frontiers in Public Health, 2021)
The advent of internet has brought an era of unprecedented connectivity between networked devices. This has initiated the development of distributed computing system and cloud computing. As a result, a dire need has evolved for remote authentication schemes in order to transfer files of sensitive nature. These files generally hold health related information between patient smart health card and cloud server communicating via smart health card solution provider. In this article the proposed approach emphasizes on the development of such a system which helps to accomplish an informal analysis. This framework helps to achieve the desired objective, provides sufficient security while maintaining usability.